2020
DOI: 10.1158/1078-0432.ccr-19-2297
|View full text |Cite
|
Sign up to set email alerts
|

Periostin and Epithelial–Mesenchymal Transition Score as Novel Prognostic Markers for Leiomyosarcoma, Myxofibrosarcoma, and Undifferentiated Pleomorphic Sarcoma

Abstract: Interpatient clinical variability in soft-tissue sarcomas (STS) highlights the need for novel prognostic markers supporting patient risk stratification. As sarcomas might exhibit a more mesenchymal or a more epithelial state, we focused on epithelialmesenchymal and mesenchymal-epithelial transitions (EMT/ MET) for prognostic clues, and selected three histotypes with variable aggressiveness.Experimental Design: The expression of EMT/MET-related factors was measured by qRT-PCR in 55 tumor samples from patients w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A corresponding linked database was constructed with IRB approval, including clinical history, hormonal therapy including THRT use, surgical, radiologic, and drug treatment, pathology data, recurrence sites and dates, and outcomes. A REMARK flow diagram of breast cancer samples and analyses are shown in Figure 1A (27).…”
Section: Breast Cancer Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…A corresponding linked database was constructed with IRB approval, including clinical history, hormonal therapy including THRT use, surgical, radiologic, and drug treatment, pathology data, recurrence sites and dates, and outcomes. A REMARK flow diagram of breast cancer samples and analyses are shown in Figure 1A (27).…”
Section: Breast Cancer Datasetsmentioning
confidence: 99%
“…A REMARK flow diagram of the patients and the observational study is shown Fig. 1A (27). The majority of patients were treated with only surgery (usually a modified radical mastectomy, as was the practice at that time) and were systemically treatment naïve, with tamoxifen given to 111/820 (13.5%) and chemotherapy administered to 64/820 (7.8%).…”
Section: Exogenous Th Supplementation Recurrence and Survival In Nodmentioning
confidence: 99%
“…The IHC score was measured as follows: (1) staining area score: 0, <5%; 1, 5–25%; 2, 25–50%; 3, 50–75%; and 4, > 70%; (2) staining intensity score: 0, no staining; 1, weak staining; 2, moderate staining; and 3, intense staining; and (3) total staining score was estimated through staining intensity and staining area. Samples with a score ≥6 were considered to indicate high expression, while those with a score <6 were considered to have low expression [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…RNA concentration and purity were measured as described above. The expression of genes linked to a mesenchymal state ( SNAI1 , SNAI2 , ZEB1 , SIP1 , α-SMA and CDH2 / N-cadherin ) and stemness ( NANOG and OCT4 ) was assessed by quantitative real-time PCR (qRT-PCR), as previously reported [ 73 ]. Primer sets used in qRT-PCR were previously published [ 73 , 74 , 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…The expression of genes linked to a mesenchymal state ( SNAI1 , SNAI2 , ZEB1 , SIP1 , α-SMA and CDH2 / N-cadherin ) and stemness ( NANOG and OCT4 ) was assessed by quantitative real-time PCR (qRT-PCR), as previously reported [ 73 ]. Primer sets used in qRT-PCR were previously published [ 73 , 74 , 75 ]. The expression levels of analysed genes are reported as a relative quantification calculated using the human porphobilinogen deaminase gene as the endogenous control with the 2 −ΔΔCt method [ 76 ].…”
Section: Methodsmentioning
confidence: 99%